Analisis Agenda Setting Pemberitaan MotoGP Mandalika Pada RRI Mataram - Hayatun Sofian; Yulanda Trisula SY; Sandi Justitia Putra; Lalu Ahmad Rahmat; I Made Putra Suryantara (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This research has an important urgency because the public will tend to pay attention to the things that are the priority of mass media coverage. The media setting agenda can relate the possible effects of influencing public opinion or opinion so that it does not only pay attention to priority news but also learns how important the way the mass media prioritizes news topics is. Formulate the problem in this study is